1991
DOI: 10.1016/0014-5793(91)80703-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PC2, a mammalian Kex2 homologue, following expression of the cDNA in microinjected Xenopus oocytes

Abstract: A human insulinoma cDNA (PC2) that encodes a protein homologous to the KexZ/subtilisin-like proteinases has recently been described [1990. J. Biol. Chem. 265.2997-30001. In order to characterise the associated proteinase activity, mRNA encoding PC2 was synthesised in vitro and microinjected into Xcnopus oocytes. The proteinase activity released into the media from oocytes microinjected with PC2 mRNA was assayed using small peptide Ruorogenic substrates. Boc.Gln.Arg.Arg aminomethyl coumarin was hydrolysed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 22 publications
(1 reference statement)
3
40
0
Order By: Relevance
“…This unusual processing pattern may be peculiar to this particular, and same cleavage site was identified in CHO cells expressing a mutant Sorting and processing of secretory proteins 11 unnatural, setting. With this proviso in mind, it is nonetheless interesting to note that in the same study it was found that mutation of Asp167, which lies at the heart of the putative PC2 active site, failed to affect the processing of the PC2 precursor, suggesting that in oocytes such processing is not autocatalytic [269]. It was, finally, also shown that the PC2 precursor was enzymically inert [269].…”
Section: Pc1/pc3 and Pc2mentioning
confidence: 91%
See 2 more Smart Citations
“…This unusual processing pattern may be peculiar to this particular, and same cleavage site was identified in CHO cells expressing a mutant Sorting and processing of secretory proteins 11 unnatural, setting. With this proviso in mind, it is nonetheless interesting to note that in the same study it was found that mutation of Asp167, which lies at the heart of the putative PC2 active site, failed to affect the processing of the PC2 precursor, suggesting that in oocytes such processing is not autocatalytic [269]. It was, finally, also shown that the PC2 precursor was enzymically inert [269].…”
Section: Pc1/pc3 and Pc2mentioning
confidence: 91%
“…There is a precise alignment of Asp, His and Ser in the catalytic domains of the different members, although a highly conserved Asn residue has been replaced by Asp in PC2, an interesting mutation since this residue has been shown to play an important role in catalysis in the bacterial subtilisins [227,228]. PCl and PC2 have an optimal enzyme activity at acidic pH [229][230][231][232], while furin has a broad, neutral pH optimum [233]. This family of enzymes has also in common the fact that Ca2l is an essential requirement, although the concentration dependency varies greatly [181].…”
Section: The Search For the Conversion Endoproteases Purification Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage of POMC in the presence of the processed form of 7B2 was partially blocked by EDTA (Fig. 1A, lane 11), an agent known to inhibit many proteolytic enzymes, including PC2 [3]. Boiling of processed 7B2 did not affect its potency to enhance POMC cleavage (Fig.…”
Section: Effect Of Recombinant 7b2 On Pomc Conversion Inmentioning
confidence: 96%
“…The activity of these subtilisin-like enzymes in the secretory pathway of neuroendocrine cells is regulated at multiple levels. PC1 and PC2 exhibit an acidic pH optimum and Ca 2+ dependence which limits their activity mainly to the transGolgi network (TGN) and the secretory granules [3][4][5][6]. Furthermore, PC1 and PC2 are synthesized as proenzymes and their activation involves proteolytic removal of the N-terminal proregion, a process that is thought to be autocatalytic [7][8][9].…”
Section: Introductionmentioning
confidence: 99%